If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + 2Y + -2X = 0 Reorder the terms: 3X + -2X + 2Y = 0 Combine like terms: 3X + -2X = 1X 1X + 2Y = 0 Solving 1X + 2Y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2Y' to each side of the equation. 1X + 2Y + -2Y = 0 + -2Y Combine like terms: 2Y + -2Y = 0 1X + 0 = 0 + -2Y 1X = 0 + -2Y Remove the zero: 1X = -2Y Divide each side by '1'. X = -2Y Simplifying X = -2Y
| Log^4(6-5x)=1 | | 46=46/5 | | 1/3/2 | | 4/5*x=16/25 | | 6/7*t=66 | | 6/7x6=66 | | 19=7+29x-16x^2 | | 16/18=n/3 | | 4/9=16/28 | | f(x)=-5x^2+3x+1 | | 1/2x4x-4 | | 100=5(d+7) | | x=(0)+6 | | (0)=x+6 | | 3y+7=55 | | (0)=1/5x-5 | | y=1/5(0)-5 | | 4a-9=33 | | (0)=2-3x | | y=2-3(0) | | (x-8)(4x+5)-(x-8)(2x-4)=0 | | x-75/12=3 | | y=-2(-2)+2 | | (11x+9)-(-2x-5)= | | 3x=18-5y | | (1-u)(5u+2)=0 | | 5-(y-1)=4y+8 | | 3a+5c-a+2c= | | 16x^2-44x-32=0 | | 15x-3=24+6x | | 15x-3=24+3 | | 7/6·x=2 |